The Model of Warehouse, Transportation, and Industry on International Trade: Study Literature Review - Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The effect of Warehouse, Transportation and Industry on International Trade is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Warehouse has an effect on International Trade; 2) Transportation has an effect on International Trade; and 3) Industry has an effect on International Trade.